2009
DOI: 10.1002/jnr.22050
|View full text |Cite
|
Sign up to set email alerts
|

Soluble mediators from human neural stem cells play a critical role in suppression of T‐cell activation and proliferation

Abstract: Human neural stem cells (hNSCs) can control inflammation in the central nervous system, although the underlying mechanisms are not understood fully. We investigated the immunomodulatory effect of hNSCs on human T cells and the underlying mechanisms. Culture supernatant from an immortalized hNSC cell line, HB1.F3, which has a therapeutic effect on acute stroke and intracerebral hemorrhage, suppressed the proliferation of allogeneically or mitogenically stimulated human peripheral T cells, including the CD3(+)CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…In fact, proliferation of T cells was inhibited by coculture with autologous or allogeneic CICs, but not with FBS tumor cells. CIC-associated factors, such as TGF-b, IL-10, IL-13, galectin, and PDGE2, which can play a negative regulatory role in the induction of tumor reactive T cells, have been described (12)(13)(14) and, notably, shown to be shared with normal stem cells as well (30). The complexity of this issue is demonstrated by the evidence that none of the molecules described above have been found to be specifically expressed or upregulated in CICs that we have isolated in vitro (data not shown), in line with the results that have been previously published by our group for GBM (10).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, proliferation of T cells was inhibited by coculture with autologous or allogeneic CICs, but not with FBS tumor cells. CIC-associated factors, such as TGF-b, IL-10, IL-13, galectin, and PDGE2, which can play a negative regulatory role in the induction of tumor reactive T cells, have been described (12)(13)(14) and, notably, shown to be shared with normal stem cells as well (30). The complexity of this issue is demonstrated by the evidence that none of the molecules described above have been found to be specifically expressed or upregulated in CICs that we have isolated in vitro (data not shown), in line with the results that have been previously published by our group for GBM (10).…”
Section: Discussionmentioning
confidence: 99%
“…Culture supernatant of human neural stem cells (HB1.F3) has a therapeutic effect on acute stroke and intracerebral hemorrhage, and suppresses the proliferation of human peripheral T cells, including the CD3 + CD103+ subpopulation [8]. After treating T cells with culture supernatant from human neural stem cells, the secretion of IL-2 was significantly decreased, whereas that of IL-4, IL-10, TNF-α, and IFN-γ was increased.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that culture supernatant of MSCs could suppress T cell proliferation in an in vitro model [8, 9], and that feline mesenchymal stem cell supernatant could inhibit reactive oxygen species production by feline neutrophils [10]. Cruz et al, suggested that human bone marrow-derived cells extracellular vesicles also ameliorate Aspergillus hyphal extract-induced allergic airway inflammation in immunocompetent mice [11].…”
Section: Introductionmentioning
confidence: 99%
“…Neural stem cells, for example, decrease the expression of TNF-α and, in consequence, reduce neutrophil infiltration into the CNS of rat models of hemorrhagic stroke [56]. Later in the course of inflammation, stem cells also suppress reactive lymphocytes while enhancing the activity and proliferation of their beneficial, regulatory subsets [57]. Moreover, trophic factors secreted by the stem cells stimulate angiogenesis and repair [58].…”
Section: Inflammation As a Target For Stem Cellsmentioning
confidence: 99%